Effect of Capital Structure, Liquidity, and Solvency on Company Value With Dividend Policy As Moderation Islamic Economic Perspective (Case Study of Manufacturing Companies Listed on the Indonesian Stock Exchange 2018-2022) - Ranidiah, Furqonti; Sumarlan, Ahmad; Khatimah, Khusnul (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to examine the influence of capital structure, liquidity and solvency on firm value with dividend policy as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2022. The population in this study consisted of 193 companies. The sampling technique used certain criteria of purposive sampling to obtain 37 companies with a 5-year research period, and resulting 185 data points. This research is quantitative uses secondary data. The data collection method used was documentation. The data analysis technique used SEM-PLS (Structural Equation Models Part Least Square) processed by using SmartPLS 3.2.9 program. The result show that capital structure has a significant positive influence on firm value. Liquidity has a significant negative influence on firm value. Solvency has a significant positive influence on firm value. Dividend policy moderates the influence of capital structure on firm value. Dividend policy does not moderate the influence of liquidity on firm value. Then, dividend policy moderates the influence of solvency on firm value.